MDR1 polymorphisms associated with risk and survival in diffuse large B-cell lymphoma. Issue 6 (1st June 2013) - Hu, Li-Li; Yu, Bingyun; Yang, Jine
Abstract: MDR1 encodes an adenosine triphosphate (ATP)-dependent efflux transporter that protects the body from environmental xenobiotics to maintain optimal health. Five single nucleotide polymorphisms (SNPs) of MDR1, T-2410C, T-129C, C1236T, G2677T/A and C3435T, were identified in our previous study. To investigate further the biological significance of these SNPs, we genotyped the SNPs in 135 patients with diffuse large B-cell lymphoma (DLBCL) and 376 age- and sex-matched controls. Statistical analysis indicated that the MDR1 -129TC genotype was associated with an increased risk of DLBCL ( p = 0.040) compared with the TT genotype, and the increased risk was more pronounced in older patients (> 50 years, p = 0.011). Patients with MDR1 2677TT displayed worse survival rates compared with those carrying MDR1 2677G/A alleles ( p = 0.036). Multivariate Cox analysis revealed that the G2677T/A polymorphism was an independent prognostic factor for overall survival (OS). Further, we found a combined effect of MDR1 G2677T/A and C3435T on OS of patients with DLBCL. These results suggest that the MDR1 T-129C, G2677T/A and C3435T polymorphisms are associated with risk of and survival in DLBCL, although the p -values are not as strong after Bonferroni correction. Further investigations with a relatively larger number of patients and longer follow-up periods should be undertaken to confirm our results.